Parent and Patient Satisfaction after Treatment for Supracondylar Humerus Fractures in 139 Children: No Difference between Skeletal Traction and Crossed Pin Fixation at Long-Term Followup - Sven Young; Jonas M. Fevang; Gunnar Gullaksen; Per T. Nilsen; Lars B. Engesæter (Advances in Orthopedics)
Aim. The aim of this study was to see whether the benefits of crossed wire fixation over skeletal traction in the treatment of pediatric supracondylar humerus fractures (SCHF) were mirrored in the children's or their caregivers' rating of the experience. Methods. As part of a study of the clinical outcome of SCHF, all the patients and the parents were asked to rate their experience of the treatment on a visual analogue scale (VAS). Results. There was no difference in the patients' or the parents' experience between the treatment groups. However there was a difference between the parents with children who experienced a neurovascular complication (mean VAS 6.1) and those that did not (mean VAS 4.3, 𝑃=0.03). The boys rated the experience as less negative (mean VAS 3.6) than the girls (mean VAS 4.7, 𝑃=0.02). Conclusion. In the long term, avoiding complications was more important to the parents than the choice of treatment for SCHF in the children.